Landscape of flavonoid metabolism in human gut microbiome and its association with health and disease - Deepika Pateriya; Vishnu Prasoodanan P. K.; Joy Scaria; Vineet K. Sharma (Gut Microbes Reports)
The positive effects of dietary flavonoids on health depend on their bioavailability in the human gut, where the flavonoid-modifying enzymes (FMEs) in gut bacteria play a crucial role in flavonoid metabolism. Thus, to comprehensively examine the role of FMEs in this process, we first constructed a database of potential FMEs containing 6,865 proteins. We identified homologs of these FMEs in gut bacterial genomes and reported species that can potentially modify flavonoids but were not previously known in this context. We examined the differential abundance of FMEs in the gut microbiomes of healthy and diseased individuals from Western and non-Western populations with distinct dietary habits. The differential enrichment of key FMEs between Western and non-Western populations and between disease and healthy samples highlights differences in gut flavonoid metabolism based on diet, population, and health status. This study reveals a comprehensive landscape of flavonoid metabolism in the human gut microbiome.